Stratigraphic correlations between the European Project for Ice Coring in Antarctica (EPICA) Dome C and Vostok ice cores showing the relative variations of snow accumulation over the past 45 kyr - Udisti R.; Becagli S.; Castellano E.; Delmonte B.; Jouzel J.; Petit J. R.; Schwander J.; STENNI, Barbara; Wolff E. (Journal of Geophysical Research, 2004)
High-resolution chemistry analysis and electrical measurements performed on two ice core records (European Project for Ice Coring in Antarctica (EPICA) Dome C and Vostok) spanning the last 45 kyr allow stratigraphic correlations by matching volcanic events. Several common events were identified along the two ice cores on the basis of acidity and sulphate spikes in snow layers. Timescales were matched through comparison with isotope (dD) profiles and using the Antarctic cold reversal (ACR) minimum, a 10Be peak, and a dust spike as temporal checkpoints. Ratios of relative snow accumulation at the two sites during the Holocene, in the glacial-interglacial transition and in the last part of the glacial period, were reconstructed by finding the best fit between Dome C and Vostok depths recording the same events. After accounting for thinning of the layers as they are buried within the glacier, the Dome C-Vostok accumulation ratio, expected to be roughly constant from the conventional accumulation-temperature-isotope approach, is 1.12 for the glacial period but increases to as much as 1.44 for a large part of the Holocene. Glaciological effects, mainly related to the geographic origin of the Vostok ice along the Ridge B-Vostok axis, can account for only a minor fraction of this change. Instead, we argue that accumulation variability between the cores stems from differential changes in atmospheric circulation during these respective climatic periods at the two sites. Regional changes in atmospheric circulation are proposed with a negative anomaly in Dome C, a positive accumulation anomaly in Vostok, or a combination of both during glacial climate. Our approach may help to improve ice core dating by: (1) revealing anomalies in accumulation-rate estimation based on the classical thermodynamic method and (2) supporting the necessity to take into account contributions due to changes in atmospheric circulation processes.